1996
DOI: 10.3950/jibiinkoka.99.552
|View full text |Cite
|
Sign up to set email alerts
|

Case Reports of Mucosal Melanoma of the Head and Neck

Abstract: Twelve patients with mucosal melanoma in the head and neck were treated at Yokohama city University from 1975 to 1994. The sex distribution was 5 male and 7 female, and the age ranged from 40 to 79 year-old. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Tables I through IV summarize the collective published experience with maxillary and sphenoid benign and malignant tumors according to histopathology and incidence. 7–50 , 51–100 , 101–150 , 151–200 , 201–250 , 251–300 , 301–350 , 351–400 , 401–450 , …”
Section: Resultsmentioning
confidence: 99%
“…Tables I through IV summarize the collective published experience with maxillary and sphenoid benign and malignant tumors according to histopathology and incidence. 7–50 , 51–100 , 101–150 , 151–200 , 201–250 , 251–300 , 301–350 , 351–400 , 401–450 , …”
Section: Resultsmentioning
confidence: 99%
“…Conley reported more men with mucosal melanoma (57%) than women with the condition (43%) [29] . Although Mochimatsu et al [30] and Gaze et al [31] reported this malignancy more in female than male [30,31] . The present study shows that 51.9% of all patients with MMHN in Kerman province were female.…”
Section: ------------------------------------------------------------mentioning
confidence: 89%
“…In our study, the most common site within head and neck region was the nasal cavity. Some studies have shown similar site distribution in the head and neck [7,8,30,31,33] . Although, it is seen in some researches that nasal cavity and oral cavity are reported as the most common site [4,22,28] .…”
Section: ------------------------------------------------------------mentioning
confidence: 93%
See 1 more Smart Citation